Barkerina dobrogiaca Neagu, 2000, a Valanginian marker taxon from the northern Neotethysian margin. (September 2019) - Schlagintweit, Felix; Bucur, Ioan I.; Granier, Bruno; Koch, Roman
Abstract: Barkerina dobrogiaca Neagu (Valanginian of Romania), a medium-sized complex benthic foraminifera, is described from the Valanginian of the Pontides, NE Turkey. Barkerina dobrogiaca differs from the type-species B. barkerensis Frizzell & Schwartz (Albian of Texas) by its small size, and comparably thin septula and test wall. The present paper is a further contribution to the knowledge of inventory and faunal assemblages of Valanginian shallow-water carbonates. Compared to the classical Urgonian (Hauterivian to lower Aptian) these are still incompletely known. Together with another form reported from the Barremian of Romania, it also shows that representatives of Barkerina Frizzell & Schwartz are well present in the Neotethysian realm.